A new look at coastal sage scrub: What 70-year old VTM plot data tell us about southern California shrublands - Taylor, R. S. (Planning for Biodiversity: Bringing Research and Management Together, 2005)
This is a preliminary report on a project to characterize the historic species composition of coastal sage scrub vegetation in southern California using plot data collected between 1929 and 1934 by the USDA Forest Service's Vegetation Type Map (VTM) survey. Records and maps from a large historic data set collected for the VTM survey were converted into a digital database and GIS coverage. Historic data for 1481 shrub plots were combined with climate, modern land use, and land cover data. Preliminary analysis found patterns of species composition and geographic distribution in coastal sage scrub considerably more detailed than have been described in previously published regional descriptions. Coastal sage scrub associations described in local studies are here shown to occur over larger areas in the southern California region than the areas within which they were originally described. Maps of the regional distributions of these coastal sage scrub associations were produced. Summer precipitation, elevation, and minimum winter temperature best predicted relative differences in abundance of Eriogonum fasciculatum and Artemisia californica. Salvia apiana preferred interior, higher elevation sites with high annual precipitation and an extremely continental climate. Salvia mellifera’s distribution was not well predicted by any environmental factors measured in this study. Rates of coastal sage scrub conversion were estimated by county and regionally for a number of species associations.
Keywords: classification; Climate; coastal sage scrub; gradient analysis; ordination; vegetation associations